MONITORING DAN KONTROL ALAT PENGERING SEPATU OTOMATIS BERBASIS IoT - Angga; Riyanto, Agus; Syamsudin, Mariana (Electrical Network Systems and Sources, 2025)
Conventional shoe drying methods generally utilise sunlight and aeration, but are often constrained by unpredictable weather and low light intensity. This causes the drying process to take a long time, even up to a week, and risks damaging the shoes, such as peeling sole glue and fading colours. In addition, the level of dryness of the shoes becomes uneven. To overcome these problems, an automatic shoe dryer system was designed using ESP32 as a monitoring and control tool. This system is equipped with an AC heater as an artificial heater, a DHT22 sensor to detect the temperature and humidity in the drying room, a 1-phase AC motor as a centrifugal force driver to reduce the moisture content in the shoes, and a 16x2 LCD to display real-time temperature and humidity data. The system is also connected to the Internet of Things (IoT) based Blynk application so that the drying process can be monitored and controlled online via smartphone. Based on 10 trials of reducing moisture content for 5 minutes, the average humidity was 93.8% RH. Meanwhile, the drying process using a heater took an average of 208.5 minutes at temperatures below 56°C with a final humidity of 79% RH. This system proved to be more efficient and practical than the manual method.